Clinical significance of serum thymus and activation‐regulated chemokine in gastric cancer: Potential as a serum biomarker. Issue 10 (1st October 2014) - Lim, Jong‐Baeck; Kim, Do‐Kyun; Chung, Hye Won
<x xml:space="preserve">Abstract</x> Thymus and activation‐regulated chemokine (TARC) can stimulate cancer cell proliferation and migration. The present study evaluated the clinical significance of serum TARC in gastric cancer (GC). We measured serum TARC, macrophage‐derived chemokine, monocyte chemotactic protein‐1 and stem cell factor (SCF) levels using a chemiluminescent immunoassay along the GC carcinogenesis (normal, high‐risk, early GC [EGC] and advanced GC [AGC]) in both training (N = 25 per group) and independent validation datasets (90 normal, 30 high‐risk, 50 EGC and 50 AGC). Serum levels were compared among groups using one‐way analysis of variance. To evaluate the diagnostic potential of serum TARC for GC, receiver operating characteristic curve and logistic regression analyses were performed. Correlations between serum TARC and GC clinicopathological features were analyzed using Spearman's correlation. In the training dataset, serum TARC correlated with serum MDC, MCP‐1 and SCF. However, only serum TARC and SCF were significantly higher in cancer groups than non‐cancer groups (P < 0.001). In the validation dataset, serum TARC also increased along the GC carcinogenesis; the AGC group (167.2 ± 111.1 ng/mL) had significantly higher levels than the EGC (109.1 ± 67.7 ng/mL), the high‐risk (66.2 ± 47.7 ng/mL) and the normal (67.5 ± 36.2 ng/mL) groups (Bonferroni, all P < 0.001). Receiver operating characteristic curves and logistic regression demonstrated the remarkable diagnostic potential of serum TARC as a single marker (72.0% sensitivity and 71.1% specificity; cutoff point, 0.37; logistic regression) and in a multiple‐marker panel (72.6% sensitivity and 88.2% specificity; cutoff point, 0.54). Spearman's correlation showed that serum TARC was closely correlated with tumor size (γs = 0.227, P = 0.028), T‐stage (γs = 0.340, P = 0.001), N‐stage (γs = 0.318, P = 0.002) and M‐stage (γs = 0.346, P = 0.001). Serum TARC is a promising serum biomarker for GC.